Partisipasi Perempuan dalam Ruang Politik (Studi Kasus di Pondok Hidayatul Muslimin 1 Parit Sembin Kubu Raya) - Jumarni Jumarni; Jagad Aditya Dewantara; Amrazi Zakso; Sulistyarini Sulistyarini; Thomy Sastra Atmaja (Journal on Education, 2024)
Women's political participation is often in the spotlight in society, especially women in Islamic boarding schools are often considered secondary creatures. Islam itself requires equal position between men and women, for example in politics. Women's participation in politics still faces a number of challenges, due to patriarchal culture which still hinders women's access to politics, especially in legislative institutions and the lack of education about politics in Islamic boarding schools. In Islamic boarding schools, the role of women in the political space in Islamic boarding schools cannot be said to be a passive contribution because there are several obstacles that must be taken into account. This study understands the role of women in politics in a small Islamic boarding school environment. This research aims to find out the forms of women's participation in the political space in Islamic boarding schools. This research method uses a qualitative method with a descriptive approach. Data collection techniques in this research used observation, interview and documentation techniques. The results of this research are that women's participation in political space in the Islamic boarding school environment is realized in an organization in the form of a student council, namely the Intra-School Student Organization. Then there is the election of room chairman and dormitory chairman as a form of minor political participation in Islamic boarding schools. The conclusion of this research is that the form of women's participation in politics within the scope of Islamic boarding schools is the existence of the OSIS organization, the election of dormitory heads, and the election of class presidents